Potentially Harmful Excipients: State of the Art for Oral Liquid Forms Used in Neonatology and Pediatrics Units - Marianne Bobillot; Violaine Delannoy; Alexandre Trouillard; Jean Marie Kinowski; Noelia Maria Sanchez-Ballester; Ian Soulairol (MDPI AG, 2024)
The pediatric population exhibits an important age-dependent heterogeneity in pharmacokinetics and pharmacodynamics parameters, resulting in differences in drug efficacy and toxicity compared to the adult population, particularly for neonates. Toxicity and efficacy divergences have been studied for active molecules, but the impact on the pharmacological parameters of excipients remains less well known. To fill this lack of knowledge, several initiatives have been started to gather information on the specific toxicity of excipients, such as the KIDS list or the STEP database. In order to contribute to this much-needed action, in this work, a compilation of the 219 formulations of oral liquid forms prescribed in pediatrics and neonatology units was established based on the summary of product characteristics. Then, for excipients found in more than 10% of the analyzed formulations, a review of their toxicity data was carried out using the STEP database. Finally, for a selection of 10 frequently used liquid forms, the amounts of excipients administered daily were calculated based on the recommended posology in the Summary of Product Characteristics (SPC) and compared with the recommended daily limits proposed by the European Medicine Agency. Pediatrics-adapted formulations are still rare, and it is not always possible to find safe alternatives to drugs containing excipients of interest.